Towards Positive Social Change: the evolution of transformation in the South African Financial Services sector - Prozesky, Justin (Graduate School of Business (GSB), 2021)
South Africa's democratic transition towards social and economic equality is under constant scrutiny, challenged by rising levels of unemployment, poverty and inequality. Since 1994 the African National Congress government has enacted various legislative interventions to change long-established racial distortions of economic opportunity and wealth accumulation, a number of which target business. The response and role of business in such an environment remains contested, both in literature and practice. There were (and are) calls for the role of businesses to evolve beyond narrow profit maximisation to play a more active part in economic and social transformation. Against this backdrop the Financial Sector Charter was collaboratively developed between the industry and its social partners in 2003 as a route map for such change. Employing a critical realism approach with a longitudinal perspective, this qualitative study explores the perspectives of key protagonists of the Financial Sector Charter on their experiences of developing and implementing the initiative: how it came into being, how it was applied and what could be done differently. Based upon semi-structured interviews with senior leaders from industry, government, black business, trade associations, labour and NGOs, the study reveals a number of issues: a deliberate attempt to leverage the capabilities and competitive forces in the industry to drive change; contestation within government over this approach; and a desire to use the capabilities of the industry to “reset” the country's current path of economic transformation. The significance of the study lies in the hitherto undocumented exposure it gives to the perspectives of the people involved in this unusual form of cross-sector social partnership and their efforts to catalyse positive social change not only in the Financial Services industry but in South Africa more broadly.